THE VALUE OF USING DAPAGLIFLOZIN SUPPLEMENTATION IN THE MANAGEMENT OF TYPEII-DIABETES WITH HYPERTENSION: A PRELIMINARYCROSS-SECTIONAL STUDY IN SULAIMANI- IRAQ - Esmail, Vian Ahmed Wasta (Journal of Sulaimani Medical College, 2024)
Background Dapagliflozin is known to have pleiotropic effects that extend to the cardiovascular system and various body organs. The presence of concomitant illnesses and complications such as hypertension with type 2 diabetes may change the magnitude of these pleotropic effects. Objectives to test the hypothesis that Dapagliflozin supplementation is of benefit in type 2 diabetes associated with hypertension compared to type 2 diabetes without hypertension. patients and Methods In this cross-sectional study, 37 diabetic patients who were receiving 10 mg of Dapagliflozin/day plus insulin and/or oral antidiabetic agents were divided into two groups: Group I (n = 15) included diabetic normotensive patients, while group II (n = 22) were diabetic hypertensive patients who were receiving one or two antihypertensive drugs as well. Anthropometric measurements, blood pressure, arterial stiffness index, myocardial work stress, hematological indices, serum fasting lipid profile, glycaemic indices, renal function tests, and Echocardiography for measuring Left Ventricular Ejection Fraction were recorded. Results Hypertension as a concomitant illness resulted in significant differences in body mass index (P= 0.045), white blood cells (P=0.003), platelet count (P = 0.011), fasting blood glucose (P= 0.036), serum triglycerides (P= 0.003), and triglyceride- glucose index (P = 0.001). Conclusion The pleotropic effects of Dapagliflozin on selected organs and blood cells were affected by concomitant hypertension and its efficacy as an oral antidiabetic agent declined in the presence of high blood pressure but maintained renal function and produced a positive impact on the haematological indices. Additionally, the antihypertensive efficacy of Dapagliflozin decreases as blood glucose and triglycerides increase.
Keywords: Dapagliflozin; Oral antidiabetic agents; Hypertension; Arterial stiffness index; Myocardial workstress; Triglycerideglucose index